Тенденции развития гостиничного хозяйства Волынской области - Ерко, Ирина Владимировна; Єрко, Ірина Володимирівна; Yerko, Iryna V. (УО "Полесский государственный университет"., 2014)
В статье произведен анализ деятельности гостиничного хозяйства Волынской области. Рассмотрены количественные и качественные показатели деятельности предприятий временного размещения региона, предложен ряд мероприятий по улучшению их развития.

In the article it is analysed activity of facilities of the temporal placing of the Volinskoy area. Quantitative and high–quality performance of enterprises of hotel economy indicators are described. The row of measures is offered on the improvement of development of establishments from the temporal placing on territory of the Volinskoy area.
Trends in the hotel industry in Volyn region
Keywords: средство размещения; Волынская область